Ocular changes in rabbits with corticosteroid-induced ocular hypertension. Issue 9 (September 1979) - Ticho, U; Lahav, M; Berkowitz, S; Yoffe, P
Abstract : Rabbit eyes with steroid-induced ocular hypertension were investigated in order to evaluate the histochemical abnormalities in the chamber angle region. The right eye of 14 rabbits was treated by dexamethasone 1% 3 times daily for 3 to 5 weeks. The eyes were stained by haematoxylin-eosin, periodic acid Schiff, fibrin, colloidal iron, and alcian blue with and without hyaluronidase. All treated eyes developed elevated intraocular pressure up to 4 weeks after treatment. These globes showed alcian-blue-positive hyaluronidase-sensitive staining in the amorphous material adjacent to Schlemm's canal and in the cytoplasmic granules of trabecular endothelial cells. There was no increase in incorporation of radioactive thymidine into nuclei of endothelial cells as seen by autoradiography. These results provide further support for the idea that there is abnormal accumulation of acid mucopolysaccharides in the chamber angle in steroid-induced ocular hypertension.